From face-to-face to online Delivery: Training of professionals in evidence-based prevention - Hein, A. W; Goycolea, R. M; Rivas, J. A; Montenegro, M. C (Adiktologie, 2022)
BACKGROUND: By disseminating the Universal Prevention Curriculums (UPC), the Colombo Plan (CP) seeks to narrow the gap between scientific knowledge on effective prevention of substance use and its application in the field. In 2020 CP adapted these training methods for online delivery. AIMS: This implementation study aimed to adapt the UPC Coordinator Series Walkthrough to an online and distance learning medium and develop a process evaluation study focused on course implementation. METHODS: A flipped classroom method combined 32 online sessions with offline tasks. Using various online applications, the study team adapted key aspects of face-to-face to an online/distance learning environment. Special attention was paid to providing sufficient technical support and scaffolding strategies to allow tech-savvy participants to engage in the training. Participants completed knowledge pre-post-tests and course assessment surveys. Session-by-session engagement was monitored, and suggestions were collected to monitor quality and improve the training approach. PARTICIPANTS: Twenty-seven academics, government officials, and NGO representatives participated in the pilot test. RESULTS: Compared to other online and face-to- face training participants, the pilot group achieved higher than expected completion rates and knowledge acquisition scores. Also, a high level of satisfaction and engagement was observed, especially regarding the peer-supported learning strategies. CONCLUSIONS: Although online training may not duplicate the face- to-face experience, interactive strategies supported by different low- cost or free applications successfully mimicked key aspects of the in-person experience. Even though the pilot group was highly skilled in using information technology, participants required constant technical support. From the training effectiveness perspective, careful consideration should be given to characteristics of participants that will be trained using online strategies, particularly if low information technology literacy may be an issue